Does Debt-IPO by Privately-held Firms Trigger Financial Statement Analysis? - WANG, Jiwei (Institutional Knowledge at Singapore Management University, 2010)
We investigate financial statement management by privately-held firms that only issue debt in an initial public offering. We examine whether managers manage financial ratios important to credit rating agency Standard & Poor’s, attempting to achieve a better credit rating. To this end, we examine whether these ratios are consistently near the worse (better) end of a benchmark sample distribution for a particular credit rating category (e.g. AAA, BBB, etc.) depending upon whether managers’ efforts are (are not) successful in attaining a better credit rating. Only the debt leverage ratios are consistently worse. Examining accounting earning management via accruals and earnings management via real economic actions we find little evidence of financial ratio manipulation. Further, we find that Standard and Poor’s does not assign overly optimistic credit ratings to debt-IPO firms (relative to other firms with debt ratings), presumably to win new business.